Book Review: Duncan Webb and David Rowe (eds) Insurance Law: Practice, Policy & Principles - Holmes, Renee (Victoria University of Wellington Law Review, 2005)
This article is a book review of Duncan Webb and David Rowe (eds) Insurance Law: Practice, Policy & Principles (The Centre for Commercial and Corporate Law Inc, Christchurch, 2004) (227 + x pages). The book is a collection of essays covering a broad range of topical insurance law issues. Holmes argues that the collection shows some aspects of insurance cases are solved by the application of principles that are unique to insurance contracts, and are often quite different to the principles applied to contracts in general. Given the diversity of the subject matter, Holmes laments the fact that there is no editorial introduction to insurance law found in this issue of the Law Review. It is concluded that the book will be relevant to a broad audience on differing levels and will be a valuable tool for practitioners, academics and students alike.